D-dimer levels at the time of admission to hospital as a predictor of outcome in trauma patients: A prospective observational study - Amarjyoti Hazarika; Mandeep Kumar; Jasmina Ahluwalia; Bisman J. K. Khurana; Varun Mahajan; Nidhi Bhatia; Navneen Naik; Deepak Kumar (Saudi Journal of Anaesthesia)
Background: Trauma causes a state of hypercoagulability, and its presence is common early in the injury course. D-dimer (DD), considered a good screening tool for coagulation activation and higher plasma levels, has been associated with unfavorable outcomes. Hence, in trauma, measuring DD levels may help provide useful prognostic information. The aim of the study was to find whether DD levels at the time of admission can predict the outcome of patients. Methods: This prospective observational studied 205 adult patients of age group 18–60 years, presenting to trauma emergency within 24 h of injury and blood samples collected within this period. The primary outcome was to assess whether DD levels at admission predicted outcome. Association of DD levels with injury severity score, with blunt or penetrating trauma, time from injury to admission, and to hospital stay were secondary outcomes. A value of DD >250 ng/ml was considered elevated. Results: The DD levels were significantly higher in patients who died than those who were discharged [2316.28 (384.5,3331.18) vs 498.03 (140,693), P = 0.001]. On receiver operating characteristic analysis, a cutoff value of 1793.35 ng/ml for serum DD was obtained with sensitivity and specificity values of 72.7% and 60.8%, respectively. The odds of death in patients were 5.87 [95% CI 1.67 to 20.51] times more when DD >1793.35 ng/ml (P = 0.002). Conclusion: Our study demonstrates that DD levels at admission were high among nonsurvivors compared to survivors. A cutoff value of more than 1793.35 ng/ml is associated with an unfavorable outcome.